Ecology, invasion history and biodiversity-driven management of the coconut black-headed caterpillar Opisina arenosella in Asia - Lu, Hui; Lyu, Baoqian; Tang, Jihong; Wu, Qiqi; Wyckhuys, Kris A. G.; Le, Khac Hoang; Chongchitmate, Patchareewan; Qiu, Haiyan; Zhang, Qikai (Frontiers in Plant Science, 2023)
The coconut black-headed caterpillar (BHC), Opisina arenosella Walker (Lepidoptera: Xyloryctidae) is an important herbivore of various palm species that originates in South Asia. Over the past decades, O. arenosella has spread to several countries in Eastern and Southeast Asia i.e., Vietnam, Thailand and China. BHC larval feeding damage can cause severe defoliation and occasional plant death, resulting in direct production losses (e.g., for coconut) while degrading the aesthetic or cultural value of urban and rural landscapes. In this review paper, we systematically describe the taxonomy, bio-ecology, invasion history and management of O. arenosella throughout Asia. The recent identification of chemical cues for BHC mating and oviposition has enabled the development of (volatile-mediated) monitoring and mass-trapping methods. While O. arenosella is routinely managed with insecticides, more sustainable management alternatives have been devised and validated e.g., crop sanitation, intercropping, cultural control or biological control. Recurrent releases of mass-produced parasitoids lower BHC infestation pressure up to 95%. Equally, a speciose complex of predacious ants provides 75-98% mortality of BHC egg masses within the palm canopy. Insect and vertebrate biological control has been effectively paired with sanitary measures and good agronomy (i.e., proper fertilization, irrigation), and promoted through participatory farmer training programs. By thus compiling historic and recent scientific findings on the ecology, prevention and control of O. arenosella, this work facilitates the implementation of cost-effective integrated pest management (IPM) strategies for an emerging palm pest of regional allure.